Application of the Controlled Source Radiomagnetotellurics (CSRMT) in the Study of Rocks Overlying Kimberlite Pipes in Yakutia/Siberia - Alexander K. Saraev; Arseny A. Shlykov; Buelent Tezkan (Geosciences, 2022)
Тhe task of searching for kimberlite pipes in covered areas of the Yakutia kimberlite province is very difficult due to the significant heterogeneity of the rocks overlying kimberlite pipes. The overlying strata of terrigenous sediments contain rocks of the trap complex (dolerite sills, tuff bodies). We consider the results of the controlled source radiomagnetotelluric (CSRMT) soundings in Yakutia/Siberia. Due to the great thickness of the overlying rocks (near 100 m) and the relatively small horizontal sizes of kimberlite pipes (80–200 m), they cannot confidently be detected directly. An additional difficulty in identifying pipe anomalies is the presence of a layer of conductive carbonaceous siltstones in the overlying strata. Therefore, the main aim of the CSRMT surveys was the study of overlying rocks and the search for indirect indications of the presence of pipes. Possibilities to study the structure of dolerite sills located within overlying sediments and to map the top edge of hosting carbonate rocks are demonstrated using the CSRMT data. The pinching out of dolerite sills above pipes («windows in traps») and the lowering of the top edge of hosting rocks at pipes can be considered as indirect indications of the presence of pipes.